Perkembangan Peradaban Islam dalam Perspektif Sosial Budaya - Saidina, Muhammad Farhan (Yayasan Albahriah Jamiah Indonesia, 2025)
Islamic civilization is one of the world’s great civilizations, not only shaping belief systems and laws but also exerting a significant influence on the socio-cultural order of societies in various parts of the world. The background of this study is based on the importance of understanding the dynamics of the development of Islamic civilization in a socio-cultural context, as an effort to trace the roots of its strength and the challenges of transformation it has faced throughout history. The purpose of this study is to analyze the development of Islamic civilization from the classical to the contemporary period, focusing on the accompanying social and cultural aspects. This research uses a qualitative method with a historical-sociological approach, namely through a literature review of relevant primary and secondary literature. The results show that Islamic civilization developed dynamically through interactions with local cultures, scientific achievements, the influence of Sufism, and the integration of Islamic values into the social structure of society. During the classical period, centers of civilization such as Baghdad, Cairo, and Cordoba became symbols of the integration of Islamic science, art, and ethics in public life. In the modern era, Islamic civilization faces the challenges of globalization, secularism, and an identity crisis, but also shows a resurgence in the form of a revitalization of Islamic values in contemporary culture through education, Islamic art, and socio-religious movements. In conclusion, the development of Islamic civilization from a socio-cultural perspective reflects Islam's ability to adapt and maintain its core values in changing times.